2018
DOI: 10.1186/s12917-018-1443-y
|View full text |Cite
|
Sign up to set email alerts
|

Long term consistency and location specificity of equine gluteus medius muscle activity during locomotion on the treadmill

Abstract: BackgroundThe equine m. gluteus medius (GM) is the largest muscle of the horse, its main movement function is the extension of the hip joint. The objective of the present study was to measure equine GM activity in three adjacent locations on GM during walk and trot on a treadmill, in order to document potential differences. Fourteen Haflinger mares were measured using surface electromyography and kinematic markers to identify the motion cycles on three occasions over 16 weeks. The electrodes were placed on lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…To our knowledge, only a few equine gait studies have described the reliability or variation observed for sEMG data, collected during treadmill locomotion [5][6][7]31]. As such, the reliability of sEMG profiles from a healthy population of horses remains largely unknown during over-ground trot.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only a few equine gait studies have described the reliability or variation observed for sEMG data, collected during treadmill locomotion [5][6][7]31]. As such, the reliability of sEMG profiles from a healthy population of horses remains largely unknown during over-ground trot.…”
Section: Introductionmentioning
confidence: 99%
“…Many training studies have been combining two or three out of the four aforementioned muscle plasticity parameters ( 5 7 ), most of them, focusing on the m. gluteus medius, known as an archetype locomotion-function type of muscle group ( 55 , 56 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, at this point, no training studies are available involving longitudinal follow-up of all four muscle plasticity parameters in multiple muscles with differing main mechanical function (muscles mainly involved in postural stability vs. muscles involved in locomotion). It can be expected that each type of training modulates a different core set of muscles ( 55 , 56 ). By involving both “main posture vs. main locomotion directed muscle groups” at the same time, a much more integrative and subtle physiological insight is obtained into how the muscular compartment adapts in response to a certain training type.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of gluteus medius (GM)may cause reduction of steps and make lateral movements or changes in directions harder. It happens because it is the main extensor muscle of the lumbosacral joint and contributes to abduction and flexion of hind limbs (Williams and Mckenna, 2016;Zsoldos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%